2018
DOI: 10.1002/imhj.21723
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Playgroup for Depressed Mothers and Their Infants: Feasibility Study and Pilot Randomized Trial of Community Hugs

Abstract: Symptoms of depression negatively impact on mother-infant relationships and child outcomes. We evaluated a novel, 10-session mother-infant therapeutic playgroup-Community HUGS (CHUGS)-which combines cognitive and experiential components through psychoeducation, play, music, and movement. Participants were mothers experiencing a range of postnatal mental health difficulties, including depression, with infants ≤12 months of age. However, the aim was not to treat maternal depression but to ameliorate associated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 48 publications
0
46
0
3
Order By: Relevance
“…59,60 Three studies were excluded because of insufficient numeric data [62][63][64] and one study was excluded because of unacceptably high risk of bias. 65 Table 2 presents participant characteristics. No studies started during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…59,60 Three studies were excluded because of insufficient numeric data [62][63][64] and one study was excluded because of unacceptably high risk of bias. 65 Table 2 presents participant characteristics. No studies started during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…60 One study was excluded from the review because of an unacceptably high risk of bias caused by lack of assessor masking and high risk of bias in relation to ‘incomplete outcome data addressed’. 65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 presents an overview of the quality of included studies. Twelve of the sixteen included studies reported the use of a randomised controlled trial (RCT) design (Challacombe et al, 2017;Ericksen et al, 2018;Fonagy et al, 2016;Goodman et al, 2015; PERINATAL MENTAL HEALTHCARE: REV INFANT OUTCOMES. 10 Letourneau et al, 2011;Murray et al, 2003;Onozawa et al, 2001;Puckering et al, 2010;Onozawa et al, 2001;Puckering et al, 2010;Stein et al, 2006;Tambelli et al, 2015;Tsivos et al, 2015;van Doesum et al, 2008), although four of these studies did not include adequate concealment of the allocation process in their design (Letourneau et al, 2011;Murray et al, 2003;Onozawa et al, 2001;Tambelli et al, 2015).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Elizabeth Loughlin, a dance movement therapist in Australia, has worked extensively with the pediatric population in several contexts. Loughlin offers therapeutic playgroups and individual DMT for depressed and anxious mothers and their infants in the hospital outpatient and psychiatric inpatient settings [64]. She also worked in medical DMT within her social work role in a pediatric hospital setting for over 20 years providing DMT programs for children and adolescents with medical conditions [57,65,66].…”
Section: Prevalence Of Dmt In Pediatric Oncology and Other Medicalmentioning
confidence: 99%